Post-curing conversion kinetics as functions of the irradiation time and increment thickness - Nicola Scotti; Alberto Venturello; Francesco Andrea Coero Borga; Damiano Pasqualini; Davide Salvatore Paolino; Francesco Geobaldo; Elio Berutti (University of São Paulo, 2013)
Objective: This study evaluated the variation of conversion degree (DC) in the 12 hours following initial photoactivation of a low-shrinkage composite resin (Venus Diamond). Material and Methods: The conversion degree was monitored for 12 hours using Attenuated Total Reflection (ATR) F-TIR Spectroscopy. The composite was placed in 1 or 2 mm rings and cured for 10 or 20 seconds with a LED lamp. ATR spectra were acquired from the bottom surface of each sample immediately after the initial photoactivation (P=0), 30 minutes (P=0.5) and 12 hours after photoactivation (P=12) in order to obtain the DC progression during the post-curing period. Interactions between thickness (T), irradiation time (I) and post-curing (P) on the DC were calculated through ANOVA testing. Results: All the first order interactions were statistically significant, with the exception of the T-P interaction. Furthermore, the shift from P=0 to P=0.5 had a statistically higher influence than the shift from P=0.5 to P=12. The post-curing period played a fundamental role in reaching higher DC values with the low-shrinkage composite resin tested in this study. Moreover, both the irradiation time and the composite thickness strongly influenced the DC. Conclusions: Increased irradiation time may be useful in obtaining a high conversion degree (DC) with a low-shrinkage nano-hybrid composite resin, particularly with 2 mm composite layers.